Hubungan Kelimpahan dan Keanekaragaman Fitoplankton dengan Kelimpahan dan Keanekaragaman Zooplankton di Perairan Pulau Serangan, Bali - Dewanti, Luh Putu Puspita; Putra, I Dewa Nyoman Nurweda; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 4 No 2 (2018)DO - 10.24843/jmas.2018.v4.i02.324-335, 2018)
Plankton is one of the biological resources that have an important role in the marine ecosystem. Plankton life is strongly influenced by the water quality parameters, one of which is the content of nutrients (nitrates and phosphates). Increased nutrient content caused by the increased load input from human activities. Serangan Island waters including the coastal ecosystem is widely used for a variety of human activities, such as tourism, aquaculture, residential, and transportation. All human activity will affect water quality will lead to an increase in nutrients and organic matter which in turn can lead to changes in water quality chemical physics and structure of plankton. The purpose of this study was to determine the relationship of the abundance and diversity of phytoplankton abundance and diversity of zooplankton and to know the physical parameters - chemical effect on the abundance of plankton. The method used is the Pearson correlation analysis to determine the relationship between abundance and diversity of phytoplankton abundance and diversity of zooplankton, and principal component analysis to look at the parameters of the water the most influence on the abundance of plankton. Results of Principal Component Analysis showed that the waters of the parameters that influence the abundance of plankton varies at each observation station. Pearson correlation analysis showed a strong relationship between the abundance of phytoplankton to zooplankton abundance with a correlation value of 0.64.